Evaluating replicability of ten influential research on sensory marketing - Motoki, Kosuke; Iseki, Sayo (Frontiers in Communication, 2022)
We attempted to evaluate the replicability and generalizability of ten influential research on sensory marketing by conducting a high-powered and pre-registered replication in online settings in non-WEIRD consumers. The results revealed that only 20% of findings could be successfully replicated, and their effect sizes are as half as the original ones. Two successful studies had relatively larger sample sizes, used sound symbolism, and employed within-participants manipulation of senses. No studies involving visual factors, between-participant manipulation of senses, or interactions between factors could be replicated. Our findings reveal an initial estimate of the replicability and generalizability of sensory marketing.